Comparing the Critical Thinking Skills of Dentistry, Engineering, and Law Students: A Cross-Sectional Study in Mashhad, Iran - Mohammad Hosein Sadeghi; Ali Kazemian; Maryam Mehrabkhani (Journal of Mashhad Dental School)
Background: Critical thinking refers to a discipline that enables students to deal with social, scientific, and practical problems effectively. This study aimed to compare the critical thinking skills of first-year and fourth-year dentistry, civil engineering and law students.Methods and Materials: This research was conducted from January 2021 to 2022. Dental students were recruited form Mashhad University of Medical Sciences, Mashhad, Iran. Civil engineering and law students were recruited from Ferdowsi University, Mashhad, Iran. All participants were either first-year or fourth-year students. Students were enrolled by a census sampling method. The Persian version of the California Critical Thinking Skills Test (CCTST) questionnaire was used for data collection. The validity and reliability of this questionnaire have been previously confirmed. The complete score for this questionnaire is a maximum of 34. The first part of the questionnaire inquired about the demographic information of students. Participants were asked to complete the web-based questionnaire anonymously. Data analysis was performed using SPSS version 21 employing statistical tests such as one-way ANOVA, post-hoc Tukey, and T-test. The significance level for all analyses was set at 0.05.Results: The online CCTST questionnaire was distributed among a total of 470 students and completed by 148 (31.4% response rate). Participants acquired an overall mean score of 11.73 ± 3.89. Dentistry students exhibited a significantly higher score than the civil engineering (P<0/001) and law students (P=%24) (13.09 ± 0.46 versus 11.29 ± 0.54 and 10.19 ± 0.49, respectively). The total score of first-year and fourth-year dentistry students was not significantly different.Conclusion: The present study showed that the level of critical thinking skills of dentistry, civil engineering, and law students was suboptimal. This problem shows that certain educational practices need to be reviewed, and more attention should be paid to training human and conceptual skills as part of education planning.